A study on drinking water quality in different income groups of Vizianagaram region of India. (10th August 2022) - Reddy, M. Kiranmai; Priyadarshini, N. Priyanka; Singh, Visakha; Suresh Reddy, K.V.N.
Abstract: Portable clean water consumption is the basic right of every individual. The major global concern is water pollution which can cause mortality. Change in physicochemical characteristics in drinking water is not only a pollution problem, but the presence of antibiotic-resistant microbes is also a significant issue. The study was carried out to assess the physicochemical and microbiological quality of the reservoir, municipality-supplied water, and bottled water. A total of 100 samples were collected from different income classes (higher, medium, and low) groups. The experiments were carried out based on the guidelines of APHA. In the present study, 40% of samples have been found to be contaminated with bacteria such as Escherichia coli, Vibrio cholerae, and Enterobacter aerogenes . Moreover, these bacteria also showed antibiotic resistance to certain drugs. The percentage of isolated bacterial strains was resistant to amoxicillin and ampicillin antibiotics. The statistical analysis of the Chi-square test states that there is a significant correlation between E. coli and other microbes ( p ≤ 0.5). This study gives a piece of baseline information about the prevalence of antibiotic-resistant bacteria and focuses on the improvement of water from purification before reaching the consumer. HIGHLIGHTS: Identification of resistance bacteria in drinking water. Differentiation in income groups, their access to drinking water and the persistence of microbes. Identification of resistance microbes was analyzed for the first time in the study area. Graphical Abstract